Sustainable Logistic Scenarios in the NSR Region - Jacob Kronbak; Angela Münch; Liping Jiang; Lisbeth Brøde de Jepsen (Next Generation Supply Chains: Trends and Opportunities. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 18, 2014)
Freight transport between North Sea Region (NSR) countries presents high trade volumes in all Standard International Trade Classification (SITC) classes. Trade volume shifts over time depending, among others, on cost trends within the transport sector, which in turn are driven by, e.g. transport regulation. The recent EU regulations target the increase of intermodal transport in order to, among others, decrease the environmental impact of freight transport. This project provides a general approach for investigating the possible changes of transport cost within the NSR region under various future scenarios. Firstly, three scenarios are proposed namely regulation, environment and competition scenarios which possess a different degree of including environmental cost into the transport cost calculation. After introducing the scenarios, the effects of the respective scenario on transport in terms of flows, modes and efficiencies is discussed. Secondly, generalized transport cost maps of intermodal transports scenarios (i.e. combination of road transport and short-sea-shipping) are calculated for 10 selected NSR ports/regions for the three different future cost developments. Maps are drawn which show the shift of transport costs and with this indicate the future stability of the trade flows. Thirdly, the shifts in the intermodal transport cost for the three scenarios are compared to changes in transport cost if only road transport is considered. Based on these calculations, management implications are drawn. It can be shown that establishing short-sea shipping links is cost stabilizing irrespective to the future cost development scenario if geographic distance is considered as major barrier to overcome.
10419/209187; https://econpapers.repec.org/RePEc:zbw:hiclpr:18
Keywords: 650; north-sea region; impedance distance; transport scenarios; intermodal transport